Peripheral artery disease, lower limb revascularization, and amputation in diabetes patients with and without coronary artery disease: a cohort study from the Western Denmark Heart Registry - Kevin Kris Warnakula Olesen; Christine Gyldenkerne; Troels Thim (BMJ Open Diabetes Research & Care, 2021)
Introduction Patients with diabetes have increased risk of lower limb revascularization and amputation due to higher risk of peripheral artery disease (PAD) and peripheral neuropathy. The additive effect of coronary artery disease (CAD) is less clear. We examined the risk of PAD, lower limb revascularization, and amputation in diabetes and non-diabetes patients with and without CAD in patients examined by coronary angiography (CAG).Research design and methods We included all patients undergoing CAG between 2003 and 2016 in Western Denmark. Patients with previous CAD, PAD, lower limb revascularization, or amputation were excluded. Patients were stratified by diabetes and CAD status and followed for a maximum of 10 years. Outcomes were PAD, lower limb revascularization, and amputation. We estimated 10-year cumulative incidences and adjusted HRs (aHRs) using patients neither diabetes nor CAD as reference.Results A total of 118 787 patients were included, of whom 41 878 (35%) had neither diabetes nor CAD, 5735 (5%) had diabetes alone, 59 427 (50%) had CAD alone, and 11 747 (10%) had both diabetes and CAD. Median follow-up was 6.9 years. Diabetes patients without CAD had higher risk of PAD (3.5%, aHR 1.73, 95% CI 1.51 to 1.97), lower limb revascularization (1.6%, aHR 1.55, 95% CI 1.16 to 2.05), and lower limb amputation (2.4%, aHR 5.51, 95% CI 4.09 to 7.43) compared with patients with neither diabetes nor CAD. CAD was associated with 2.5-fold and 1.8-fold higher risk of PAD and amputation, respectively, among patients without diabetes, and associated with 3.9-fold and 9.5-fold higher risk of PAD and lower limb amputation among patients with diabetes.Conclusions Despite absence of obstructive CAD, patients with diabetes remained at higher risk of PAD, lower limb revascularization, and lower limb amputation. Diabetes was more strongly associated with amputation than CAD, but CAD exacerbated the risks of PAD, revascularization, and amputation in patients with diabetes.